Comparison of Efficacy of Daily Sofosbuvir and Declatasvir with Alternate Day Sofosbuvir and Declatasvir in Hepatitis C Patients on Hemodialysis in Pakistani Population - Muhammad Muzammil, Muhammad Tahir, Nadeem Ullah, Malik Muhammad Arif, Talha Rasheeq, Muhammad Mumtaz Ather, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: compare the efficacy of daily Sofosbuvir plus Declatasvir with alternate day Sofosbuvir and Declatasvir in HCV patients on hemodialysis. Study design: Randomized clinical trial Place and duration: department of general medicine Nishtar hospital, Multan from March 2020 to March 2021 in one year duration. Methodology: A total of 260 patients were enrolled in study and divided into two groups (1 and 2) by convenient sampling technique. Non probability consecutive sampling technique was used. Group 1 treated with Sofosbuvir plus Declatasvir daily and group 2 was treated with alternate Sofosbuvir and Declatasvir. SPSS version 23.1 was used for data entry and analysis. Results: The liver enzymes and hematological parameter were noted after 24th weeks. The mean differences at baseline and after 24th weeks within the groups was statistically significant, (p<0.001). Viral load detectable, RVR, ETR, and SVR at 24 weeks was 91.5% vs 88.5%, 98.5% vs 98.5% and 97.7% vs 90.8% respectively. Conclusion: In Pakistani population hepatitis C virus is endemic like some other countries. In hemodialysis patients daily Sofosbuvir with daclatasvir is safe and effective with greater SVR as compare to Sofosbuvir with daclatasvir in alternate days even in genotype 3. Keywords: Sofosbuvir, Daclatasvir, HCV, Hemodialysis, Genotype 1,2,3